Strategi Pengembangan Aspek Lingkungan di Titik Pandang Panenjoan dengan Berlandaskan Konsep Pariwisata Bertanggung Jawab - Irham Nur Prasetyo Wibowo (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2018)
Panenjoan is one of the tourist destinations located within the Geopark Ciletuh-Palabuhanratu. This destination is located in the village of Tamanjaya, Ciemas District, Sukabumi Regency, West Java. Since the area was established as part of the Geopark Ciletuh-Palabuhanratu, an increasing number of tourists visit continues to happen every year. Negative e ects can occur if the destination is not ready in accepting such a surge, especially environmental aspects. Therefore, the study aims to formulate a development strategy for Panenjoan view point based on the concept of responsible tourism that focused on environmental aspects. This research uses qualitative research methods with data derived from the results of focused group discussion or FGD, the eld observation, and the study of the literature. Data analysis was done with the SWOT analysis and the results obtained are then elaborated in descriptive. The results obtained from this research is based on a matrix of IFAS and EFAS can note that the position of the internal and external Point of view Panenjoan tend to be weak and threatened with a score each amounting to 2.15 and 2.28. To address and minimize such threats and weaknesses, has drawn up recommendations that focus on environmental aspects of responsible tourism i.e. (1) conserving water aspect consisting of organic mulch-making training, partnership with agencies in the procurement of electronic water meter, increasing public awareness in conservation of water, and the involvement of travelers in the preservation of water. (2) The aspect of using energy e ciently which consists of working with agencies to procure light Light Emitting Diode (LED) as well as in the regular maintenance of electronic tools, and installation of the light sensor. (3) Reducing and managing waste aspect, namely waste management training, digitalization of information contents, procurement of simple recycling facility, and the separating wastes speci cally.